Earlier Experience of Robotic Inguinal Hernia Repair With the New Hugo™ Robotic System in Europe - Valentina Ferri; Emilio Vicente; Yolanda Quijano; Faruk Hernandez; Hipolito Duran; Eduardo Diaz; Isabel Fabra; Luis Malave; Pablo Ruiz; Luca Ballelli; Alessandro Broglio; Camilla Farè; et al. (Journal of Abdominal Wall Surgery)
IntroductionMinimally invasive robotic surgery has increasingly gained acceptance in abdominal wall surgery. The Hugo™ robotic system, with its modular design, offers enhanced maneuverability and flexibility, making it a promising alternative platform for inguinal hernia treatment. This article aims to present our experience with robotic inguinal hernia repair using the Hugo™ system, focusing on clinical outcomes and the challenges encountered during the learning curve.Materials and MethodsSince the introduction of the Hugo™ system in our department in January 2023, all patients undergoing robotic inguinal hernia repair with this platform have been prospectively enrolled in this study. Preoperative, intraoperative, and postoperative data were collected and analysed to assess the outcomes.ResultsA total of 69 inguinal hernia repairs were performed using the Hugo™ system in 40 patients, including 29 bilateral and 11 unilateral inguinal hernias. The median console time was 37 min for unilateral hernia while the total procedure time was 45 min (range 30–70 min). The median console time was 94 min for bilateral hernia while the total procedure time was 121.1 min (range 65–236 min). The median docking time for the robotic system was 9.5 min (range: 4.8–20.1 min). No intraoperative complications were observed and only postoperative hematoma was identified and treated.ConclusionRobotic inguinal hernia repair with the Hugo™ system is a safe, reproducible, and effective procedure. For teams with a strong background in robotic surgery, the learning curve with the Hugo™ system is rapid, allowing for efficient adaptation of the system to the existing workflow.